FEATURES OF FREE TIME PEDAGOGY IN THE CONDITIONS OF HEALTH PRESERVING STUDY OF STUDENTS - Zavydivska, N.; Zavydivska, O.; Khanikiants, O. (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2019)
The aim of this work was to develop and experimentally check the integrative pedagogical technology of organization of physical culture and health activities, which helps to optimize the process of forming a culture of free time of students. Material and methods: 168 people (students and graduates of higher educational institutions) participatedin the research. The pedagogical experiment was conducted during 2016–2017 years. Methods were used: theoretical, empirical and methods of mathematical statistics. Results. It is proved that the pedagogy of forming the culture of free time of students should consider the hierarchy of interconnections between the three spheres of life: cognitive, emotional and motor. After the completion of the pedagogical experiment 86,8% of students of the experimental group and 34,4% of the control group appreciated that knowledge obtained during the studying would help them properly organize recreational activities during leisure. Conclusions. Modeling the process of health preserving students’ study on the principles of free time pedagogy helped to form their readiness for using active forms of leisure. A positive dynamics in data of self-esteem of educational level in the issues of leisure organization by the students of the experimental group is observed. The high level of such education after the completion of the experiment was indicated by 73,1% of the interviewed students of the experimental group, compared with 29,3% – before the experiment.The statistical-probabilistic analysis (Student’s Criterion, Chuprov’s coefficient, factor analysis, etc.) of the data confirmed it representativeness and reliability, and pointed to the positive impact of the culture of free-time formation program of students.